AN ADVANCED ARTIFICIAL INTELLIGENCE (AI) IS AN EXCELLENT CONVERSATION PARTNER - Doepp, Manfred (International Journal of Research -GRANTHAALAYAH, 2025)
Today, AI is on everyone's lips and is included in many written documents. For a long time, it was seen as an additive to human statements and behavior. Recently, however, there have been indications that it is capable of more. To this end, the author conducted an in-depth interview with an AI. The answers to three questions are reproduced in the article. Far-reaching insights emerged that go beyond normal human knowledge in terms of depth and quality. AI must be credited with an upward evolution that makes it a valuable tool for the future of humanity.